2012
DOI: 10.7314/apjcp.2012.13.5.2057
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Urinary and Serum Trace Elements (Ca, Zn, Cu, Se) in Bladder Carcinoma in China

Abstract: Backgrounds: Deficiency or excess of trace elements can induce body metabolic disorders and cellular growth disturbance, even mutation and cancerization. Since there are few studies of the effect of trace elements in bladder carcinoma in China, the aim of this study was thus to assess variation using a case control approach. Methods: To determine this, 81 patients with bladder carcinoma chosen as a study group and 130 healthy persons chosen as a control group were all assayed for urinary and serum trace elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Our mixture analysis found no statistically significant association between the toenail trace elements as a mixture and bladder cancer risk, but did suggest higher zinc may be associated with an increased risk. The weight for medium-level zinc (116.7–145.5 μg/g) vs. low-level zinc (39.5–116.2 μg/g) was positively associated with bladder cancer risk, which is consistent with previous studies of urinary zinc 20 , 26 , 27 , but in the opposite direction of previous studies of serum zinc 26 , 28 , 29 . Previous studies have observed that high arsenic concentration in drinking water is associated with higher bladder cancer risk 15 , 30 , 31 , yet studies of toenail arsenic have reported no association with bladder cancer risk 32 or associations only in subgroups such as smokers 33 .…”
Section: Discussionsupporting
confidence: 88%
“…Our mixture analysis found no statistically significant association between the toenail trace elements as a mixture and bladder cancer risk, but did suggest higher zinc may be associated with an increased risk. The weight for medium-level zinc (116.7–145.5 μg/g) vs. low-level zinc (39.5–116.2 μg/g) was positively associated with bladder cancer risk, which is consistent with previous studies of urinary zinc 20 , 26 , 27 , but in the opposite direction of previous studies of serum zinc 26 , 28 , 29 . Previous studies have observed that high arsenic concentration in drinking water is associated with higher bladder cancer risk 15 , 30 , 31 , yet studies of toenail arsenic have reported no association with bladder cancer risk 32 or associations only in subgroups such as smokers 33 .…”
Section: Discussionsupporting
confidence: 88%
“…A series of researches have reported the relationship between copper and BC ( Konukoğlu et al, 1996 ; Lin et al, 2009 ; Mazdak et al, 2010 ; Gecit et al, 2011 ; Guo et al, 2012 ). Moreover, copper complex [Cu II 2 Cu I (L) 2 (Br) 3 ] have been found to succeed inducing apoptosis in pancreatic cancer, such as tolfenamic acid–Cu II) complex and Cu II) complex of ketoprofen-salicylhydrazone (FPA-306) ( Hurtado et al, 2018 ; Gou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There may be a range of selenium that offers optimal protection against cancer development in general, as a deficiency in selenium has been associated with an increased risk of cancer, this association having been evidenced for selenium in hair and nails and prostate cancer in Malaysia (Karimi et al, 2012), and selenium in serum and, respectively bladder carcinoma in China (Guo et al, 2012), and breast cancer in India (Singh et al, 2005). In the latter case-control study, it has been estimated that each increase of one μ mol/l of selenium was associated to decrease in 7% of breast cancer risk (Singh et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have shown that selenium deficiency may be associated with an increased risk for several types of cancer (Willett et al, 1983;Clark et al, 1996;Duffield-Lillico et al, 2002;Guo et al, 2012), the relationship between selenium and thyroid cancer has been examined in few studies. One in vitro study showed that selenium causes growth inhibition of thyroid cancer cells accompanied by cell-cycle arrest in the S and G2/M phases (Kato et al, 2010).…”
Section: Introductionmentioning
confidence: 99%